If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3.3(-2g + -9) + 3.9g = 0 Reorder the terms: -3.3(-9 + -2g) + 3.9g = 0 (-9 * -3.3 + -2g * -3.3) + 3.9g = 0 (29.7 + 6.6g) + 3.9g = 0 Combine like terms: 6.6g + 3.9g = 10.5g 29.7 + 10.5g = 0 Solving 29.7 + 10.5g = 0 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-29.7' to each side of the equation. 29.7 + -29.7 + 10.5g = 0 + -29.7 Combine like terms: 29.7 + -29.7 = 0.0 0.0 + 10.5g = 0 + -29.7 10.5g = 0 + -29.7 Combine like terms: 0 + -29.7 = -29.7 10.5g = -29.7 Divide each side by '10.5'. g = -2.828571429 Simplifying g = -2.828571429
| g(x)=-2x^2-12x-16 | | 9x=8x-18 | | X^2-11x+35=5 | | (6x^2)-7x-3=0 | | X^2-11+35=5 | | 6+4x=(6x+9)/3 | | 49-(2x+16)=2(x+4)+x | | (5y/7)-15=5y+30 | | (5x+4)-(8x-6)= | | -4x^2+9x-1=0 | | 5k-(3k-5)= | | 7.3x=58.4 | | 5y^2-2y^3-7y^2+5y^3= | | 5(z-4)+7z-2= | | Y-2x=-1 | | 2x^2-12=5x | | 159-(7x+6)=7(x+9)+ | | 5w^2+3=-8w | | 2(3m+4)-3(m-5)= | | 8-(2x-6)=1-3x | | 3.7x=74.0 | | 4u^2-11u=3 | | x^2-12x-22.5=0 | | 2x^2-11x-63=0 | | 2(4z+7)-4(2-5)= | | 8x=-11y-16 | | 7*12+5= | | 124-(6x+16)=6(x+5)+x | | 3(3y-1)=6y | | 6p^2=-23p-15 | | 3(-4)(-6)= | | 6.4x-2.3x=73.8 |